2013
DOI: 10.1140/epjb/e2012-30482-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic anomalous scaling in a ferromagnetic thin film model

Abstract: Recently, the interest on theoretical and experimental studies of dynamic properties of the magnetic domain wall (MDW) of ferromagnetic thin films with disorder placed in an external magnetic field has increased. In order to study global and local measurable observables, we consider the (1 + 1)-dimensional model introduced by Buceta and Muraca [Physica A 390 (2011) 4192], based on rules of evolution that describe the MDW avalanches. From the values of the roughness exponents, global ζ, local ζ loc , and spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…They have found that at the depinning transition the model predicts τ = 1.29 ± 0.02 and α = 1.55 ± 0.05, which are similar to the results obtained experimentally in films where exchange interactions dominate [9,12,13,20]. In our previous work [49] we showed that the BM model has anomalous scaling in its local statistical observables, similarly to the QEW equation and the driven RFIM but with different anomalous class. The BM model has intrinsic anomalous scaling, while the QEW equation has super-rough anomalous scaling [50] and the driven RFIM does not have an anomalous scaling univocally defined [42].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…They have found that at the depinning transition the model predicts τ = 1.29 ± 0.02 and α = 1.55 ± 0.05, which are similar to the results obtained experimentally in films where exchange interactions dominate [9,12,13,20]. In our previous work [49] we showed that the BM model has anomalous scaling in its local statistical observables, similarly to the QEW equation and the driven RFIM but with different anomalous class. The BM model has intrinsic anomalous scaling, while the QEW equation has super-rough anomalous scaling [50] and the driven RFIM does not have an anomalous scaling univocally defined [42].…”
Section: Introductionsupporting
confidence: 86%
“…n ′ j = max(n j−1 , n j , n j+1 )). These rules applied over a lattice with randomly distributed defects lead to the same properties as those obtained by the BM model: avalanches and scaling anomalies, with similar quantitative conclusions [6,49].…”
Section: The Modelsupporting
confidence: 66%
“…Following earlier reports of roughness scaling analyses [44,40,45], a generalized formalism distinguishes the global, local, and reciprocal scaling behaviors of the self-affine interface, characterized by global, local, and reciprocal scaling exponents, respectively. In this picture, standard Family-Vicsek scaling is given by all three exponents being equal.…”
Section: Scaling Of B(r) For Super-rough Interfacesmentioning
confidence: 99%
“…45 In order to further verify the anomalous scaling behavior of growth of the MoS 2 lms, we investigated the collapse of the HHCF and PSD dependent functions for different growth times. Under anomalous scaling, HHCF is given as, 46 Hðr; tÞ ¼ r 2a g A r . t…”
Section: Scaling Studies Of Mos 2 Lm Growth Using Afm Image Analysismentioning
confidence: 99%
“…Hence the function H(r,t)/r 2a when plotted as a function of À r=t 1 z Á in log-log scale for different deposition times should collapse into single curve and from their slopes both a and a loc can be estimated. 39 Similarly, PSD function can also be expressed under anomalous scaling as, 39,46 PSDðk; tÞ ¼ k…”
Section: Scaling Studies Of Mos 2 Lm Growth Using Afm Image Analysismentioning
confidence: 99%